Fantastic Bodies. The Body as a Tool of Social Criticism in Two Fantastic Short - Lynette Grivell (Brumal: Revista de Investigación sobre lo Fantástico)
One of the characteristics of the Fantastic is its subversive nature when dealing with contemporary social issues and taboo subjects, which is particularly noticeable in narratives written by women. This comparative analysis of short stories by two women writers from Central America —«Manual de hijo muerto» by Claudia Hernández (El Salvador) and «Para elegir la muerte» by María Eugenia Ramos (Honduras)— will discuss how women use narratives of violation of the body as a tool of social and cultural criticism against the authorities and the patriarchy. Framing the discussion within the field of body studies, particularly the works of Margo DeMello (2014), Bryan Turner et al. (2012), and Jean Franco (2013), this study examines how these writers deploy Fantastic narrative techniques to reflect upon the social and political turmoil in Central America during and after their internal conflicts of the 1980s.